2021
DOI: 10.1136/rmdopen-2020-001455
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of colchicine for moderate to severe COVID-19: a randomised, double-blinded, placebo-controlled clinical trial

Abstract: ObjectiveTo evaluate whether the addition of colchicine to standard treatment for COVID-19 results in better outcomes.DesignWe present the results of a randomised, double-blinded, placebo-controlled clinical trial of colchicine for the treatment of moderate to severe COVID-19, with 75 patients allocated 1:1 from 11 April to 30 August 2020. Colchicine regimen was 0.5 mg thrice daily for 5 days, then 0.5 mg twice daily for 5 days. The primary endpoints were the need for supplemental oxygen, time of hospitalisati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
187
0
8

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(222 citation statements)
references
References 26 publications
11
187
0
8
Order By: Relevance
“…Our results are supported by the results of two smaller clinical trials showing reductions in the need for oxygen supple mentation, the duration of hospital treatment, and the deterioration of clinical status. 19,20 Colchicine has previously been shown to reduce acute lung injury in an experimental model of acute respiratory-distress syndrome. 18 The risk of viral inflammatory pneumonitis therefore appears to be lowered by colchicine in patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results are supported by the results of two smaller clinical trials showing reductions in the need for oxygen supple mentation, the duration of hospital treatment, and the deterioration of clinical status. 19,20 Colchicine has previously been shown to reduce acute lung injury in an experimental model of acute respiratory-distress syndrome. 18 The risk of viral inflammatory pneumonitis therefore appears to be lowered by colchicine in patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Results for the secondary endpoints in this group of patients represented a posthoc analysis. The secondary efficacy endpoint of the need for mechanical ventilation occurred in ten (0•5%) of 2075 patients in the colchicine group, as compared with 20 (1•0%) of 2084 patients in the placebo group (table 3). Although not a prespecified endpoint, the rate of hospital admission due to any cause was 101 (4•9%) of 2075 patients in the colchicine group versus 132 (6•3%) of 2084 patients in the placebo group (OR 0•76, 95% CI 0•58-0•99; p=0•040).…”
Section: Figure: Trial Profilementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, prospective randomized controlled trials (RCT) are needed to approve colchicine in the treatment of COVID-19. In the literatüre, there are 2 RCTs whose results have been published [ 26 , 27 ]. The first study is from Greece, and the second is from Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no placebo arm, and patients were not blind to the treatment allocation. In the latter study, a double-blinded, placebo-controlled RCT, it was found that colchicine diminished the duration of oxygen support and hospitalization day [ 27 ].…”
Section: Discussionmentioning
confidence: 99%